2019
DOI: 10.1200/jco.18.00551
|View full text |Cite
|
Sign up to set email alerts
|

National Survey of Oncologists at National Cancer Institute–Designated Comprehensive Cancer Centers: Attitudes, Knowledge, and Practice Behaviors About LGBTQ Patients With Cancer

Abstract: PURPOSE To identify potential gaps in attitudes, knowledge, and institutional practices toward lesbian, gay, bisexual, transgender, and queer/questioning (LGBTQ) patients, a national survey of oncologists at National Cancer Institute–Designated Comprehensive Cancer Centers was conducted to measure these attributes related to LGBTQ patients and desire for future training and education. METHODS A random sample of 450 oncologists from 45 cancer centers was selected from the American Medical Association’s Physicia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
124
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 116 publications
(135 citation statements)
references
References 42 publications
8
124
1
Order By: Relevance
“…Several gaps in content areas readily covered in other disparity populations, including experiences of health care discrimination, access to care, and stigma, have received little research attention for SGM cancer populations, despite the inclusion of SGM as a health disparity population . Nearly all the research in this review covered SM, not GM (transgender, nonbinary gender) groups; this is a major gap in the literature, as has been previously suggested . In addition, construct development and measurement of topics salient to cancer survivors have not been fully explored in the SGM population .…”
Section: Discussionmentioning
confidence: 94%
“…Several gaps in content areas readily covered in other disparity populations, including experiences of health care discrimination, access to care, and stigma, have received little research attention for SGM cancer populations, despite the inclusion of SGM as a health disparity population . Nearly all the research in this review covered SM, not GM (transgender, nonbinary gender) groups; this is a major gap in the literature, as has been previously suggested . In addition, construct development and measurement of topics salient to cancer survivors have not been fully explored in the SGM population .…”
Section: Discussionmentioning
confidence: 94%
“…Recent studies of LGBT competency among oncologists in the United States have shown that oncologists have a high level of interest in receiving LGBT cancer health education, and showed overall limited knowledge of LGBT cancer health needs . This is problematic, as the number of people who identify as LGBT is growing, as are the number of cancer diagnoses in the United States . Based on conservative estimates, there may be over 1 million LGBT cancer survivors living in the United States …”
Section: Introductionmentioning
confidence: 99%
“…This is problematic, as the number of people who identify as LGBT is growing, as are the number of cancer diagnoses in the United States . Based on conservative estimates, there may be over 1 million LGBT cancer survivors living in the United States …”
Section: Introductionmentioning
confidence: 99%
“…A national study showed that 78% of clinicians felt that their patients would refuse to disclose their SGM status, in stark contrast to only 10% of patients reporting that they would refuse to disclose their status, citing improved individualized care as a benefit to disclosure . In a recent national survey of nearly 150 oncologists from National Cancer Institute‐designated cancer centers across the United States, Schabath and colleagues measured the attitudes, knowledge, institutional practice behaviors, and interest in education on the care of LGBTQ patients with cancer . They found that although a majority of oncologists, approximately two‐thirds, felt that it was important to know a patient's gender identity, only about one‐third felt that it was relevant to them to know of the patient's sexual orientation.…”
mentioning
confidence: 99%